P253 Investigating the complexity of the relationship between gastro-oesophageal reflux and cf lung disease. (15th November 2017) - Lord, RW; Treadway, S; Pearson, JS; Barry, PJ; Bianco, B; Whorwell, PJ; Jones, RB; McNamara, PS; Beynon, R; Smith, JA; Jones, AM
Abstract : Background: There has been a suggested connexion between gastro-oesophageal reflux (GOR) and CF lung disease. Lung disease can result in increasingly negative inspiratory thoracic pressures. These create gastro-oesophageal pressure gradients along which gastric contents may move. Then if aspirated reflux may have the potential to cause lung damage. We aimed to assess if there is a relationship between GOR and markers of lung disease severity. Methods: We are conducting a prospective observational study in stable adult CF patients, measuring GOR with combined pH and impedance (pH-MII). In preliminary analyses, we have compared reflux measures (total, proximal, supine and supine proximal events) and retrospective data including routinely collected lung function and number of courses of intravenous antibiotics. Results: 51 patients were recruited with 36 patients (mean age 30 years, mean FEV1 54% predicted, 28 males) completing all measures. Total number of reflux episodes were increased in 58% (median 81, IQR 55–105) compared to established normative values (<75 episodes). 'High risk' reflux (increased proximal or supine proximal events) was noted in 47%. Increasing reflux and higher number of IV courses in the preceding year displayed a positive trend (r=0.300, p=0.075), but this relationship was not seen for number of courses over 2 years. Curiously, patients with greater numbers of reflux events exhibited less decline in lung function over the preceding year (r=0.416, p=0.016). None of the reflux measures were correlated with baseline lung function. Conclusions: We have demonstrated that patients with stable CF lung disease have high rates of total reflux events in comparison to normative values. Almost half have reflux which has the potential to be high risk for aspiration. There was a suggestion that increased reflux events maybe associated with increased exacerbation risk. However our data also suggests, in complete contrast, that increased reflux relates to less progression of lung disease – this is not in keeping with commonly held beliefs. Further studies will be needed to unpick what is undeniably a complex relationship.